Sultan, Scholar, and Sufi: Authority and Power Relations in al-Suyūṭī’s Fatwā on Waqf - Hernandez, Rebecca Skreslet (Islamic law and society, 2013)
This essay examines a legal opinion (fatwā) by the accomplished fifteenth-century polymath, Jalāl al-Dīn al-Suyūṭī (d. 911/1505). In his treatise, the author investigates the issue of whose stipend should be given priority in endowed institutions that receive funding from the state Treasury in times of financial crisis. He argues that the scholar should have priority in deference to his learning, even if he does not fulfill the obligations stipulated in the endowment. I argue that al-Suyūṭī’s fatwā, viewed within the context of personal conflicts in his own life, reveals much about the jurist’s efforts to assert moral and persuasive authority, as well as about larger struggles between different sectors of late Mamluk society. Both in his writing and in practice, al-Suyūṭī defends the role of the righteous scholar against the worldly power of the state and against the corruption of the Sufi students under his supervision.